Yersinia pseudotuberculosis Typing Using Multi-Locus Variable-Number Tandem Repeat Analysis - V. V. Evseeva; M. E. Platonov; S. V. Dentovskaya; A. P. Anisimov (Проблемы особо опасных инфекций, 2015)
Estimated has been efficacy of MLVA25 method, used for differentiation and clusterization of Yersinia pestis strains, in reference to Yersinia pseudotuberculosis strains, as well as the search of Y. pseudotuberculosis strains mostly closely related to Y. pestis . Applied was the reduced version of the technique deploying 14 out of 25 VNTR loci. Comparative study of 71 Y. pseudotuberculosis isolates and five Y. pestis strains by means of MLVA25 and MLVA14 variants revealed 75 and 54 genotypes, respectively. Y. pseudotuberculosis strains of certain serovars corresponded to certain clusters of MLVA types. According to MLVA14 typing of 221 Y. pseudotuberculosis isolates the clusters including the strains belonging to MLST types ST19 (serovar O:3) and ST43 (serovar O:1b) were the most closely related to Y. pestis .